Gene amir_2071 of Actinosynnema mirum DSM 43827 encodes a dimethylallyltryptophan synthase superfamily protein responsible for the production of prenylated tyrosine - Melnyk, Sofiia; Rebets, Yuriy; Bratiichuk, Dmytro; Luzhetskyy, Andriy; Ostash, Bohdan (Folia microbiologica, 2025)
Actinosynnema mirum DSM 43827 is a bacterium from the small genus Actinosynnema within the rapidly growing actinomycete family Pseudonocardiaceae (Land M et al. Stand Genomic Sci 1:46-53 2009). Despite its diverse repertoire of specialized metabolite biosynthetic gene clusters (BGCs), the potential of A. mirum for production of bioactive molecules is not fully explored. Here, we used a heterologous expression approach to gain deeper insight into this issue. In this work we report that expression of in silico predicted BGC#4 from A. mirum in S. albus Del14 and S. lividans ΔYA9 led to production of several prenylated derivatives of tyrosine. Their most likely structures, according to MS and MS/MS data, agreed with 4-O-prenyl-(L)-tyrosine and its N-acetyl derivative, previously described in lichen-forming fungi (Iacovelli R et al. J Nat Prod 87:2243-2254 2024). Further experiments confirm the production of the aforementioned compounds is governed by a single structural gene, amir_2071 for prenyltransferase of dimethylallyltryptophan synthase (DMATS) superfamily, whose homologs are abundant in bacterial genomes.